Spatial Dependence of Dynamic Nonlinear Rock Weakening at the Alpine Fault, New Zealand. Issue 14 (22nd July 2021) - Simpson, Jonathan; van Wijk, Kasper; Adam, Ludmila
Abstract: We perform laser ultrasonic measurements to investigate the spatial dependence of dynamic nonlinear weakening in rocks from the Alpine Fault, New Zealand. Rocks outside the damage zone display no nonlinear weakening. Within the damage zone (<30 m from the fault), cataclasites present a 3% reduction in shear modulus from wave amplitudes inducing 1–2 microstrain at atmospheric pressure. This nonlinear elasticity decreases with a characteristic pressure between 1 and 2.5 MPa. We show that rock weakening is therefore strongest in the near surface. However, this significant elastic nonlinearity in cataclasites at low strains confirms that rock weakening may play an important role in earthquake processes, such as fault weakening, triggering of slip, rupture propagation, and coseismic velocity decreases. Plain Language Summary: Passing seismic waves can cause rocks to temporarily weaken, a phenomenon known as dynamic nonlinear rock weakening. Using rock samples from the Alpine Fault in New Zealand, we investigate how rock weakening varies with distance to the fault and depth in the Earth. We do this using lasers to generate and record ultrasonic waves in our rocks in the laboratory. Close to the fault (<30 m), fractured and granular cataclasite rocks show a 3% reduction in strength (shear modulus) during the passage of medium‐intensity waves (1–2 microstrain). As depth in the Earth increases, we find that the amount of weakening in the cataclasites decreases; rock weakening is strongest in the several hundred meters below the surface. For rocks further from the fault, we do not observe any weakening. The nonlinear changes in rock strength we observe, though they may appear small, are important for understanding processes such as the triggering of critically stressed faults by seismic waves and fault rupture propagation. Key Points: We present the first laboratory measurements of dynamic nonlinear weakening in a suite of whole fault rocks under in situ pressure. A 3% reduction of shear modulus occurs in damage‐zone cataclasites at the surface but weakening reduces rapidly with depth. These results will contribute toward understanding the role of dynamic rock weakening in earthquake processes.